Numerical and experimental investigation on laminar hot-gas flow with injected water spray - Bundhurat D. (2014)
One-dimensional space-marching technique is acquired to set up computational fluid dynamics (CFD) code to describe the characteristics of the high-temperature gas flow with injected water spray. General equations of conservation have been proposed to describe the flow characteristics. Binary diffusion, developed by Chapman and Enskog, is used to calculate the evaporation rate of water droplets. The model of drag on immersed body is used to describe the action of momentum transfer between gas and liquid phases. The flow is treated as laminar flow and the gas is treated as an ideal gas in order to achieve the computational results. To provide the comparative data for the CFD, high-temperature laminar gas flow through a 9.8-cm inside diameter pipe is arranged in adiabatic environment. Spray of water with the average of 0.07-0.08 mm droplet diameter is injected downstream into the flow at the rate of 7.2 ml/s. Momentum and heat transfers occur between hot gas and water droplets due to the difference of velocity and temperature. Droplets evaporate and are accelerated during traveling with the flow, causing the flow characteristics change of the gas phase. Both numerical and experimental results share similarity of the characteristics of the flow, including temperature, density and velocity of the flow. © 2010, INSInet Publication.